Psycho sociological aspects of the «Prison people or/and released people - Rubio Arribas, Fco. Javier (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The fact of being in prison, the lack of liberty, is one of the worst and more unpleasant experiences that a person can live, even thought for some of them it that will have to deal with it, and assume it as a part of their life. The prison expose the person to a split between family, from their family, their friends, work (with its possible lost in case the person had one), from the social surrounding, and it forces to a new schedule with new time tables, and with circumstances that were not chosen by the person, , that can in most cases be novice for the health ( Both mental and physic) . That’s why they have to adapt to a new environment that is perceived as hostile (So they have to get into it un-trustily, distance and opposition to the professionals and the main institution.